Effect Of Doxorubicin On Canine Transmissible Venereal Tumor - SWAMY MADHU; SHARMA SANJAY; SHAHI APRA (International Journal of Pharma and Bio Sciences, 2012)
The present study was undertaken to determine the effectiveness of doxorubicin as a chemotherapeutic agent against canine transmissible venereal tumor. The study was conducted in eighteen dogs of either sex with cutaneous growths confirmed as canine transmissible venereal tumor (CTVT) either cytologically or histopathologically. The animals were treated with doxorubicin hydrochloride @ 30 mg/m² at 3 week intervals, intravenously with normal saline and observed till complete regression of growth. The dogs were further observed till six months follow up period for reoccurrence of tumorous growth. Blood and biopsy samples of tumorous dogs were collected for hematological, biochemical, cytological & histopathological studies on day 0, 7 and 14. Efficacy of doxorubicin against CTVT was observed with minimal side effects as evidenced by complete regression in growth by maximum three doses of the drug .No recurrence of growth was observed in thirteen cases till six months. The chemotherapeutic agents enhanced the tumor regression by affecting the tumor cell proliferation as well as increasing the tumor cell death